THE USE OF PHOTOGRAPHIC IMAGES TO IMPROVE STUDENTS’ LEARNING OUTCOMES IN THE LESSON OF THE RELATION BETWEEN ECONOMIC ACTIVITIES AND NATURAL RESOURCES - Dinata, Sukarsih (Prodi Teknologi Pendidikan, 2016)
Abstract. This research is motivated by problems in the study of economic activity relation to natural resources that are conventional. Based on early research on learning outcomes, students who pass the study only reached 38.9%. This study aimed at improving student learning outcomes in economic activity with regard learning resource in class IV Semester II SDN Cilengkrang Northern District of Sumedang Sumedang Regency. Learning by using photographic images selected researchers to overcome these problems. The method used is the method of discussion. The steps of the learning that students in groups discussing the photographic image and then the presentation. Photographic images are an effective means of mass communication and is often used as a teaching aid that will allow teachers to deliver the material. The method used in this research is a classroom action research methods to the design of the research procedure refers to the spiral model Kemmis and McTaggart. The instruments used are guidelines for observation, interview and test. As for data validation, used techniques chek members, triangulation, audit trail and expert opinion. Based on the implementation of the actions performed by three cycles, as a whole has shown an increase from the initial data, both process and outcomes of learning. So the use of photographic images can improve student learning outcomes in material connection with the economic activity of the natural resources in the second half of the class IV SDN Cilengkrang Northern District of Sumedang Sumedang Regency. Keywords: Image Photography, Social Education, Economic Activity. Abstrak. Penelitian ini dilatarbelakangi oleh masalah pada pembelajaran kaitan aktivitas ekonomi dengan sumber daya alam yang bersifat konvensional. Berdasarkan penelitian awal pada hasil belajar, siswa yang tuntas belajar hanya mencapai 38,9 %. Penelitian ini bertujuan meningkatkan hasil belajar siswa pada pembelajaran kaitan aktivitas ekonomi dengan sumber daya alam di kelas IV Semester II SDN Cilengkrang Kecamatan Sumedang Utara Kabupaten Sumedang. Pembelajaran dengan menggunakan gambar fotografi dipilih peneliti untuk mengatasi masalah tersebut. Metode yang digunakan yaitu metode diskusi. Adapun langkah-langkah pembelajarannya yaitu siswa berkelompok berdiskusi mengenai gambar fotografi kemudian presentasi. Gambar fotografi adalah alat komunikasi massa yang efektif dan biasa digunakan sebagai alat bantu mengajar yang akan memudahkan guru untuk menyampaikan materi. Metode penelitian yang digunakan dalam penelitian ini adalah metode penelitian tindakan kelas dengan rancangan prosedur penelitiannya mengacu pada model spiral Kemmis dan McTaggart. Instrumen yang digunakan yaitu pedoman observasi, pedoman wawancara, dan tes. Sedangkan untuk validasi data, digunakan teknik member chek, triangulasi, audit trail dan expert opinion. Berdasarkan pelaksanaan tindakan yang dilakukan sebanyak tiga siklus, secara keseluruhan telah menunjukan adanya peningkatan dari data awal, baik dalam proses maupun hasil belajar. Sehingga penggunaan gambar fotografi dapat meningkatkan hasil belajar siswa pada materi kaitan aktivitas ekonomi dengan sumber daya alam di kelas IV semester II SDN Cilengkrang Kecamatan Sumedang Utara Kabupaten Sumedang. Kata Kunci: Gambar Fotografi, Pendidikan IPS, Aktivitas Ekonomi.